Cep78 knockout causes sterility and oligoasthenoteratozoospermia in male mice - Min Liu; Zongzhuang Wen; Dapeng Zhao; Wei Tian; Qingfeng Lv; Chunling Zhang; Xueyan Zhang; Fengling Meng; Hui Liu; Jiangang Gao; Zhiwei Yao (Scientific Reports, 2025)
Abstract Oligoasthenoteratozoospermia (OAT) is a common cause of infertility among males, and the majority of cases of idiopathic OAT are thought to be attributed to genetic defects. In this study, the role of the CEP78 protein in spermatogenesis was initially investigated using Cep78 knockout (Cep78 −/− ) mice. Notably, the male Cep78 −/− mice exhibited the OAT phenotype and sterility. To elucidate the mechanisms underlying the functions of the Cep78 gene in spermatogenesis, the histomorphology of germ cells was investigated during different stages of mitosis, meiosis, and spermiogenesis. Apoptotic assays and RNA-sequencing analyses were additionally performed using the testicular tissue samples of control and Cep78 −/− mice. The findings strongly suggested that defects in the Cep78 gene can lead to male infertility with OAT and that the CEP78 protein is essential for acrosomal biogenesis, sperm head shaping, and formation of flagella during spermiogenesis. The findings are expected to expand the spectrum of genetic defects in OAT and enhance the accuracy of genetic screening and clinical diagnosis.